If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3i+6=7(1-2)
We move all terms to the left:
3i+6-(7(1-2))=0
We add all the numbers together, and all the variables
3i+6-(7(-1))=0
We add all the numbers together, and all the variables
3i+13=0
We move all terms containing i to the left, all other terms to the right
3i=-13
i=-13/3
i=-4+1/3
| 22-3x=x+6 | | 18+7-x=12-112 | | 900x=1800 | | 101+58+58=x | | 9.t=81 | | 101-58=x | | 99/9*2=27x | | 9k+21=-33 | | 101+58=x | | (4x+16)+(7x-1)=180 | | 4x+3=15–2x | | 3r+2–r=-4 | | (0.5)^3x+2=8^(5x-4) | | –8−3n=10−5n | | (2x-39)°(3x+14)= | | 2x+12=88 | | x^2+23=123 | | 2f+13=-11 | | 130+40=y | | x/5+x+1/3=2 | | –5c=–8c+9 | | 7x-13=4x= | | 7-20x*4=-128+27 | | h-(-13.94)=21.06 | | 36+63=y | | 3.6d=2.7 | | 25-6a=7 | | x+18.99=14 | | 34-y/2=-12 | | 2y–12=22 | | 3x+28=5x-16 | | .4=32b |